Monitoring Aggression in Adolescents: Yoga as I Panacea (Global Journal of Human-Social Science, 2012)
An Anova of the order of 2x2x 2 with repeated measure was employed in the present research to gauge the effect of yogic exercises if any between the control group and the experimental group in the two genders from pre to post test on different types of aggression This investigation used a complete package of multiple counselling techniques to normalize aggression The sample consisted of 100 school students 50 males 50 females from Shimla district of H P between the ages of 14 to 17 years the main findings are 1 The main effects of group gender and treatment have turned out to be significant at 05 and 01 levels 2 the interaction effects of treatment x group and treatment x gender have also yielded significant F ratios thereby revealing the significant impact of interventions in monitoring the aggression